2015
DOI: 10.1371/journal.pone.0123344
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Hormones, Apolipoproteins, Adipokines, and Cytokines in the Alveolar Lining Fluid of Healthy Adults: Compartmentalization and Physiological Correlates

Abstract: ObjectivesOur current understanding of hormone regulation in lung parenchyma is quite limited. We aimed to quantify a diverse array of biologically relevant protein mediators in alveolar lining fluid (ALF), compared to serum concentrations, and explore factors associated with protein compartmentalization on either side of the air-blood barrier.Research Design and MethodsParticipants were 24 healthy adult non-smoker volunteers without respiratory symptoms or significant medical conditions, with normal lung exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
(43 reference statements)
0
12
0
1
Order By: Relevance
“…74 For example, the concentration of APOE in ELF from healthy adults ranges from 10 to 80 ng/mL (0.3-2.4 nmol/L), with a median concentration of 60 ng/mL (1.8 nmol/L). 36 Here we show that concentrations of APOE similar to levels present in ELF from healthy subjects neither activated the NLRP3 inflammasome nor induced secretion of mature IL-1b from BALF macrophages from asthmatic subjects. In contrast, APOE at concentrations of 25 nmol/L or greater induced cleavage of pro-IL-1b to its mature 17-kDa form, which was secreted from cells.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…74 For example, the concentration of APOE in ELF from healthy adults ranges from 10 to 80 ng/mL (0.3-2.4 nmol/L), with a median concentration of 60 ng/mL (1.8 nmol/L). 36 Here we show that concentrations of APOE similar to levels present in ELF from healthy subjects neither activated the NLRP3 inflammasome nor induced secretion of mature IL-1b from BALF macrophages from asthmatic subjects. In contrast, APOE at concentrations of 25 nmol/L or greater induced cleavage of pro-IL-1b to its mature 17-kDa form, which was secreted from cells.…”
Section: Discussionmentioning
confidence: 53%
“…8 Instead, we found that APOE activated the NLRP3 inflammasome in BALF macrophages and induced IL-1b secretion when concentrations exceeded levels that had previously been found in ELF from healthy subjects. 36 Furthermore, using a murine viral exacerbation model of HDM-induced neutrophilic airway inflammation, we show that APOE concentrations in mouse ELF are sufficiently high to activate the NLRP3 inflammasome in ex vivo cultures of BALF macrophages from asthmatic subjects.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although there is no evidence of GLP-1 production within the lung, it appears to be in much higher concentrations within bronchoalveolar fluid as compared to the serum in one study of healthy adults (Mendivil et al, 2015; Richter et al, 1993). It is not known how these levels might change in unhealthy conditions, but reductions in GLP-1 production with obesity and diabetes likely are paralleled within the lung and may contribute to dysfunction.…”
Section: Glucagon-like Peptide 1 and The Lungmentioning
confidence: 92%
“…Plasma leptin concentrations and the leptin/adiponectin ratio exhibited a significantly inversed correlation with initial FEV1 in emphysema patients [ 37 ]. Leptin was detected in the alveolar lining fluid of healthy humans [ 38 ] and was induced in injured human and murine lungs [ 39 ]. In rat alveolar macrophages and murine peritoneal macrophages models, leptin increased phospholipase activity and enhanced the group IVC iPLA2 (cPLA2γ) protein expression, resulting in upregulated alveolar macrophage leukotriene synthesis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%